Sexual Abuse of Older Residents in Nursing Homes: A Focus Group Interview of Nursing Home Staff - Maria Helen Iversen; Astrid Kilvik; Wenche Malmedal (Nursing Research and Practice)
The objective of this study was to increase knowledge of sexual abuse against older residents in nursing homes. A qualitative approach was used. Through a focus group interview with staff in nursing homes, the aim was to reveal employees’ thoughts, experiences, and attitudes. Findings from the focus group interview show that sexual abuse of older residents is a taboo topic among health professionals. Acts of sexual abuse are difficult to imagine; it is hard to believe that it occurs. The fact that staff are not aware that it could happen, or have a hard time believing that it actually happens, can amplify the residents’ vulnerable position as potential victims of abuse, and it makes it even more challenging to report or uncover such acts. The study highlights the need for education of all health care workers in Norway as well as more research on sexual abuse against older residents in nursing homes. Furthermore, there is a need for good policies and reporting systems, as an important step towards addressing sexual abuse of the aged in a more appropriate way. Further research must aim to reveal more about this taboo area.